How densely do manufacturing establishments occupy land? - Kristian Behrens; Florian Mayneris; Théophile Ndjanmou Biéda (Université du Québec à Montréal, École des sciences de la gestion (ESG UQAM), Département des sciences économiques, 2024)
We construct a new dataset containing parcel sizes and building footprints of Canadian manufacturing plants and decompose industrial density (parcel size per worker) into: crowding (floorspace per worker); building height (floorspace to building footprint); and parcel coverage (building footprint to parcel size). We find that establishments occupy parcels more densely in big cities and central locations, and that larger establishments use less land per worker. Floorspace per worker is unrelated to distance from the city centre. The estimated elasticity of substitution between land- and non-land factors is small, between 0.14 to 0.42.
Keywords: R32; R14; L60; 330; Land use; industrial density; georeferenced data; building and parcel polygons; production function